Breaking the Silence: A Social Network Analysis of Self-Harm on X - Ike Mardiati Agustin; Ikhwan Yuda Kusuma; Fajar Rinawati; Irmawan Andri (Universitas STRADA Indonesia, 2025)
Background: Self-harm, commonly referred to as non-suicidal self-injury (NSSI), is a severe mental health issue impacting millions of people worldwide. In addition, Social Network Analysis (SNA) is an effective tool for examining social interactions and connections on social media platforms such as X in order to examine the diffusion of information, development of communities, identification of important influencers, and the analysis of sentiment on social media. Purpose: This research aims to analyze the communication, actions, and attitudes of X users around self - harm. To accomplish this objective, social network analysis was used to explore the link between self-harming behaviors and social media by studying the interactions between people and groups. Methods: This research collected data using NodeXL Pro software (Social Media Research Foundation, Redwood City, CA) that allows for collecting tweets from X. Results: This research gives insight into X conversations, habits, and feelings around self- harm. Research on social networks revealed that individual and news media accounts dominate self-harm material, sources, trends, and patterns. The data also indicate that self-harm is strongly associated with cyberbullying victimization, teen dating violence, and sexual abuse, all of which predominantly impact adolescents. Conclusion: The significance of health organizations and experts engaging in social media dialogues in order to deliver accurate information and services to those in need.